Sesamoid Rotation Angle: A Valuable Parameter for Assessing Sesamoid Displacement in Hallux Valgus - Cheng-Min Shih; Shun-Ping Wang; Cheng-En Hsu; Kun-Hui Chen; Cheng-Hung Lee (Formosan Journal of Musculoskeletal Disorders)
Background: Sesamoid bone displacement from the weight-bearing dorsoplantar (DP) radiography is known to be correlated with the severity of hallux valgus deformity. The sesamoid rotation angle (SRA) is a new radiographic parameter with continuous values for evaluating sesamoid positions in a weight-bearing tangential view. However, the relationships are not clear among the SRA, hallux valgus angle (HVA), intermetatarsal angle (IMA), and sesamoid displacement scale. Objectives: We aimed to analyze the relationship between the SRA and various conventional radiographic parameters. Materials and Methods: Weight-bearing DP and tangential radiographs were obtained from 72 patients (113 feet) aged 15–70 years (average 48.9, standard deviation 15). The HVA, IMA, Hardy’s 7-position scale, and lateral sesamoid position (LSP) were measured. These parameters were then correlated with the SRA. We also compared SRA distributions across different severity grades based on the various parameters. Results: The SRA was significantly correlated with the HVA (r = 0.669), IMA (r = 0.562), LSP (r = 0.711), and Hardy’s scale (r = 0.721), all with P < 0.01. Analysis of the variance of SRA distribution revealed significant differences among the subgroups of the HVA, IMA, and LSP. SRA distributions were similar among Hardy’s scale 2–4. Conclusions: We suggest that patients with SRA >30° should be considered as having hallux valgus of a high grade or at least a moderate grade. SRA distributions, however, were similar among Hardy’s scale 2–4. We recommend the use of SRA as an easy and quick screening tool for assessing moderate-to-severe hallux valgus.